Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

Follow the trail of responses and if you have anything to add please sign up or sign in.

You can ask your own question or look at similar Maths questions.

simplify the equation as:

2x-3x^2-12x+5=0

multiply the whole equation with -1

3x^2-2x+12x_5=0

3x^2+10x-5=0

use the quadratic formula and solve it


x= −5/3 −2/3 Γ10 or −5/3 2/3 Γ10

Γ = square root

You need to expand, simplify then use the quadratic equation.

Expand the brackets: 2x-3x^2-12x=-5 This gives you

3x^2+10x-5=0 and then you use the quadratic formula in order to find x :-)

Footer Graphic